2009
DOI: 10.1507/endocrj.k09e-140
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Reduces ER Stress in the Liver: Direct Monitoring of in vivo ER Stress Using ER Stress-activated Indicator Transgenic Mice

Abstract: Abstract. it is known that endoplasmic reticulum (eR) stress is provoked under diabetic conditions and is possibly involved in the development of insulin resistance. in this study, using eR stress-activated indicator (eRai) transgenic mice which express green fluorescent protein under ER stress conditions, we directly evaluated the effects of a diabetic agent pioglitazone on in vivo eR stress under diabetic conditions. in high fat and high sucrose diet-induced diabetic eRai transgenic mice, 8 weeks of pioglita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…The adipocyte form, PPAR␥2, is induced in liver in the setting of traditional WD-induced hepatic steatosis, and, whereas selective elimination of PPAR␥2 by gene targeting reduces hepatic steatosis, its loss also worsens lipotoxicity and insulin resistance (28,43,50,53,68). Ligand-induced activation of PPAR␥ may also ameliorate hepatic ER stress (31,67). Our results suggest a nutritional switch that regulates hepatic PPAR␥ splice isoforms.…”
Section: Discussionmentioning
confidence: 72%
“…The adipocyte form, PPAR␥2, is induced in liver in the setting of traditional WD-induced hepatic steatosis, and, whereas selective elimination of PPAR␥2 by gene targeting reduces hepatic steatosis, its loss also worsens lipotoxicity and insulin resistance (28,43,50,53,68). Ligand-induced activation of PPAR␥ may also ameliorate hepatic ER stress (31,67). Our results suggest a nutritional switch that regulates hepatic PPAR␥ splice isoforms.…”
Section: Discussionmentioning
confidence: 72%
“…Loffler et al have also found significant down-regulation of ER stress genes in the livers from diabetic db/ db mice treated with rosiglitazone [10]. Yoshiuchi et al have reported that pioglitazone treatment suppressed ER stress in the liver by using ER-stress-activated indicator transgenic mice [28]. This is why they had suggested that the suppression of ER stress might explain, at least in part, the pharmacological effects of pioglitazone in reducing insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the underlying molecular mechanism of how casein induces ER stress or how rosiglitazone attenuates this change was not clearly defined in our study. It may be possible that increased levels of serum adiponectin influenced the reduction of ER stress in the liver, [28]. Lastly, we did not quantify the degree of casein-induced ER stress and hepatocyte apoptosis.…”
Section: Casein Injection Induces Hepatic Er Stress and Rosiglitazonmentioning
confidence: 98%
“…UPR is an important tightly regulated response required for cellular homeostasis, and it intersects with many other pathways that are critical for glucose metabolism, glycogen synthesis, lipid metabolism, inflammation, and metabolic disease 45. Recent studies have shown that the UPR plays a role in liver disease,46, 47 that its activation is associated with hepatic insulin resistance and fatty acid flux,48, 49 and that the UPR mediator XBP1 can up‐regulate hepatic lipogenic factor 47, 50. Our study suggests that overexpression of MAN1A1 leads to steatosis, inflammation, and HCC formation, possibly through the UPR, perhaps evoking the transcriptional networks involved in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%